Beyond CAR T Cells: Other Cell-Based Immunotherapeutic Strategies Against Cancer - Patel, Shabnum; Burga, Rachel A.; Powell, Allison B.; Chorvinsky, Elizabeth A.; Hoq, Nia; McCormack, Sarah E.; Van Pelt, Stacey N.; Hanley, Patrick J.; Cruz, Conrad Russell Y. (Frontiers in Oncology, 2019)
BACKGROUND: Chimeric antigen receptor (CAR)-modified T cells have successfully harnessed T cell immunity against malignancies, but they are by no means the only cell therapies in development for cancer. MAIN TEXT SUMMARY: Systemic immunity is thought to play a key role in combatting neoplastic disease; in this vein, genetic modifications meant to explore other components of T cell immunity are being evaluated. In addition, other immune cells – from both the innate and adaptive compartments – are in various stages of clinical application. In this review, we focus on these non-CAR T cell immunotherapeutic approaches for malignancy. The first section describes engineering T cells to express non-CAR constructs, and the second section describes other gene-modified cells used to target malignancy. CONCLUSIONS: CAR T cell therapies have demonstrated the clinical benefits of harnessing our body’s own defenses to combat tumor cells. Similar research is being conducted on lesser known modifications and gene-modified immune cells, which we highlight in this review.